Implication Of International Scholars' Influence On The Direction Of Abdul Hadi's Political Thought - Latifah Abd Majid; Zuliza Mohd Kusrin; Wan Siti Norjannah W Sulong; Mohd Nasir Abd Majid (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by MyCite